Ciri Finir Kupas Kayu Jabon (Anthocephalus cadamba) - Abigael Kabe; Wayan Darmawan; Muh. Yusram Massijaya (Institut Pertanian Bogor, 2013)
Fast growing jabon is largely rotary-cut to produce veneer for plywood, com-ply, and LVL. In order to provide better information on veneer production and utilization, in this study the effects of wood juvenility and veneer thickness on lathe checks of jabon rotary-cut veneer were evaluated. Before veneer manufacturing, the jabon log was boiled at 50 and 75 °C for 4 and 8 hours respectively. The boiled logs were peeled to produce veneer of 1 and 2 mm thick. Lathe checks of veneers were measured under an optical video microscope. The rotary-cut veneer was grouped and evaluated separately at every segmented ring of 1 cm from pith to bark. The results showed that wood juvenility and veneer thickness had an important effect on lathe checks for the rotary-cut veneer. In general, the number of lathe check of the veneer increases with increasing veneer thickness and increase from pith to bark. Boiling of logs before rotary-cutting could decrease the value of lathe check. The results indicated that boiling of logs at 50 °C for 8 hours, and at 75 °C for 4 and 8 hours could minimize the number of lathe checks in manufacturing of 1 and 2 mm rotary-cut veneer from juvenile wood jabon.